KEBERTERIMAAN KOSAKATA BAKU BAHASA INDONESIA DI KALANGAN GURU SMA/SMK/MA PESERTA SOSIALISASI DAN TES UKBI DI KOTA PALU - NFN Nurmiah (Multilingual, 2016)
AbstractThis study was conducted to know the acceptability of standard Indonesian vocabulary among teachers SMA/ SMK / MA as participant of socialization and test UKBI in Palu. The method used is descriptive method that done quantitatively. The data collection is done by using instruments in questionnaire form. The questionnaire consisted of questions related to personal data of respondents and nine pairs form standard Indonesianvocabulary. The nine forms of vocabulary can be specified into as absorptions of foreign languages whichconsist of three vocabularies, as morphological system consist of three vocabularies, and as the differentspelling forms consist of three vocabularies. The results of this study indicate that the ninth of standardIndonesian vocabulary there are four forms of vocabulary has not been accepted among teachers SMA / SMK/ MA as participant of socialization and test UKBI in Palu, such as salat, telanjur, komplet, dan mengebom.The reason of teachers choose vocabulary which not standardized (shalat, terlanjur, komplit, and membom)are they have not know language rules and their language use habit.